Effect of gases on crystallization of heat-resistant chromium steels - E. I. Marukovich; V. Y. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2023)
It has been shown that the main influence on the crystallization of heat‑resistant chromium steels is hydrogen. It is a demodifying element of the casting structure. The mechanism of the influence of hydrogen on the crystallization of heat‑resistant chromium steels can be explained from the position of nanostructured crystallization of casting alloys. Dissolved hydrogen atoms, adsorbing on elementary nanocrystals of iron and chromium in melts of heat‑resistant chromium steels, prevent the combination of nanocrystals into nuclei of crystallization of α‑phase microcrystals. As a result, castings with an unmodified structure are obtained. Reduction of hydrogen concentration in melts of heat‑resistant chromium steels contributes to formation of modified structure in castings at their hardening.